2012
DOI: 10.4014/jmb.1107.07018
|View full text |Cite
|
Sign up to set email alerts
|

Cells Transformed by PLC-Gamma 1 Overexpression are Highly Sensitive to Clostridium difficile Toxin A-Induced Apoptosis and Mitotic Inhibition

Abstract: Phospholipase C-γl (PLC-γl) expression is associated with cellular transformation. Notably, PLC-γ is up-regulated in colorectal cancer tissue and breast carcinoma. Because exotoxins released by Clostridium botulinum have been shown to induce apoptosis and promote growth arrest in various cancer cell lines, we examined here the potential of Clostridium difficile toxin A to selectively induce apoptosis in cells transformed by PLC-γl overexpression. We found that PLC-γl-transformed cells, but not vectortransforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…This finding was similar to another study showing that BtxA inhibits the growth of LNCaP human prostate cancer cells in vitro and in vivo (Karsenty et al, 2009). Moreover, BtxA has been shown for induces apoptosis in cells transformed by PLC-γI overexpression (Nam et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding was similar to another study showing that BtxA inhibits the growth of LNCaP human prostate cancer cells in vitro and in vivo (Karsenty et al, 2009). Moreover, BtxA has been shown for induces apoptosis in cells transformed by PLC-γI overexpression (Nam et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…This interest stems from the fact that BtxA inhibits the growth of LNCaP human prostate cancer cells in vitro and in vivo and induces apoptosis in a dose-dependent manner (Mazo et al, 2008;Karsenty et al, 2009;Proietti et al, 2012). Moreover, BtxA has been shown for up-regulate 167 genes and down-regulate 60 genes relevant to focal adhesion, cell adhesion molecules, adherents and gap junction related pathways in carcinoma cell lines (Thirunavukkarasusx et al, 2011;Gorgal et al, 2012;Nam et al, 2012;Tegenge et al, 2012). The * objective of this study was to test the activity of BtxA against breast cancer cell proliferation underlying this phenomenon as a trial for developing a novel functional anticancer drug.…”
Section: Introductionmentioning
confidence: 99%
“…In three studies, investigators injected BoNT into a malignant tumor and demonstrated cellular apoptosis and reduction of tumor size [57][58][59] (Table 3). In another six studies, adding BoNT-A to cancer cell cultures reduced cell growth, induced apoptosis, and inhibited mitosis in various cancer cell lines: Prostate, breast, colon, and pancreatic tumors [60][61][62][63][64][65]. In one study, transfection of insulin secreting cells by BoNT-A reduced insulin secretion, suggesting a potential for treatment of insulinomas [66].…”
Section: The Effects Of Botulinum Neurotoxins Injections On Malignantmentioning
confidence: 99%
“…In addition, the treatment of BotxA is extensively being used as therapeutics against in several diseases such as hyperkinetic movement, pain, epilepsy, and glandular hyperactivity disorders (Mittal and Jabbari, 2020). In addition to the therapeutic actions of BotxA, its anticancer action in several cancer types such as breast cancer and glioblastoma (Nam et a. 2012;Akpınar et al 2020;Mittal and Jabbari, 2020).…”
Section: Introductionmentioning
confidence: 99%